2019
DOI: 10.3386/w25844
|View full text |Cite
|
Sign up to set email alerts
|

The Illusion of Stable Preferences over Major Life Decisions

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The correspondence between timing desires and pregnancy weakens when assessed on a one-year time frame and might deteriorate further over longer time horizons. Women's fertility desires are flexible and sensitive to changing life circumstances (Mueller et al 2019;Trinitapoli and Yeatman 2018). Heightened recognition of the flexibility and contingency of fertility desires, however, does not mean that desires cannot be highly predictive in the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…The correspondence between timing desires and pregnancy weakens when assessed on a one-year time frame and might deteriorate further over longer time horizons. Women's fertility desires are flexible and sensitive to changing life circumstances (Mueller et al 2019;Trinitapoli and Yeatman 2018). Heightened recognition of the flexibility and contingency of fertility desires, however, does not mean that desires cannot be highly predictive in the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…Reported be liefs were sig nif cantly shifted by the in ter view ers' knowl edge, with their es ti mated rates de creas ing by about nine per cent age points, or roughly 0.3 stan dard de vi a tions of the con trolgroup be lief dis tri bu tion. This result can help ex plain the puz zling fnd ing that peo ple's pref er ences and be liefs ap pear to be very un sta ble in panel sur veys (Chuang and Schecter 2015;Mueller et al 2019). If recorded re sponses are heavily shaped by in ter view ers' knowl edge and be liefs, then peo ple's an swers may ap pear to be much more un sta ble than they re ally are.…”
Section: Introductionmentioning
confidence: 91%
“…Few studies assessed the stability of preferences over some duration using repeated assessment of the same individuals [19,29]. To our knowledge, only one study has compared within-person versus betweenperson preferences over time [19]. Although the study population was very different, a comparable pattern was observed.…”
Section: Does the Relative Importance Of Those Domains Change Within ...mentioning
confidence: 99%
“…Two studies have evaluated patient recovery priorities at a single timepoint [7,26]. Few studies assessed the stability of preferences over some duration using repeated assessment of the same individuals [19,29]. To our knowledge, only one study has compared within-person versus betweenperson preferences over time [19].…”
Section: Does the Relative Importance Of Those Domains Change Within ...mentioning
confidence: 99%